Technology and people : an analysis of the forest workforce, technology and the sourcing decision in forest harvesting in South Africa - Manyuchi, Killian Tendai (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScFor)--Stellenbosch University, 2002.